2003
DOI: 10.1002/cncr.10990
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and carboplatin in advanced transitional cell carcinoma of the urinary tract

Abstract: BACKGROUND Cisplatin‐based combinations are considered to be the standard treatment for advanced transitional cell carcinoma (TCC) of the urothelium. Many of the patients are elderly with concomitant diseases or impaired renal function. We studied the tolerance and activity of the gemcitabine/carboplatin combination as a therapeutic alternative. METHODS Patients with locally advanced or metastatic TCC of the urothelium were treated with gemcitabine 1000 mg/m2 on Days 1 and 8 and carboplatin area under the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 21 publications
3
49
0
1
Order By: Relevance
“…The study was closed early, and no conclusions could be made 26 . Similarly, a carboplatin regimen was investigated alongside gemcitabine in phase ii trials that did not exclude patients fit to receive cisplatin, resulting in ors of 56% and 59% and a median os of only 10 months [27][28][29] . In a phase ii randomized trial of gc versus gemcitabine with carboplatin, better response rates were observed with gc (66% vs. 35%) without significant differences in toxicity profile 30 .…”
Section: 21mentioning
confidence: 99%
“…The study was closed early, and no conclusions could be made 26 . Similarly, a carboplatin regimen was investigated alongside gemcitabine in phase ii trials that did not exclude patients fit to receive cisplatin, resulting in ors of 56% and 59% and a median os of only 10 months [27][28][29] . In a phase ii randomized trial of gc versus gemcitabine with carboplatin, better response rates were observed with gc (66% vs. 35%) without significant differences in toxicity profile 30 .…”
Section: 21mentioning
confidence: 99%
“…22, 23 The studies reviewed reported nausea in 14%, 6 nausea and vomiting in 10% to 47%, 2,8,9 grade 3 to 4 nausea and vomiting in 7% to 65%, 2,5 vomiting in 32%, 3 and grade 3 or 4 vomiting in 7% of patients. 3 Appropriate acute emesis prophylaxis includes a serotonin antagonist and a corticosteroid plus or minus a neurokinin antagonist in selected patients. 22,23 One of the following regimens is suggested: The antiemetic therapy should continue for at least 2 days after day 1.…”
Section: Supportive Care a Acute And Delayed Emesis Prophylaxismentioning
confidence: 99%
“…The GCarbo regimen ( Table 1) has been studied in metastatic bladder cancer [1][2][3][4][5][6] and is recommended as an alternative regimen to first-line chemotherapy in metastatic disease. 7 The GCarbo regimen has also been studied as perioperative chemotherapy, specifically neoadjuvant chemotherapy, in locally advanced bladder cancer prior to cystectomy.…”
Section: Indication(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Three small phase 2 trials comparing cisplatin with carboplatin reported similar overall RRs (ORRs), with less toxicity noted in the carboplatin arms. [19][20][21] A European Organization for Research and Treatment of Cancer (EORTC) phase 3 trial of M-VAC versus carboplatin and paclitaxel closed early because of poor accrual. 22 Trials of carboplatin-based regimens in patients with normal renal function have demonstrated encouraging ORRs in the range of 30% to 40%, but the CR rates are lower and they are paralleled by shorter median survivals of 8 months to 10 months.…”
Section: Chemotherapy For Bladder Cancer Chemotherapy For Metastatic mentioning
confidence: 99%